THE INFLUENCE OF SALES GROWTH AND INFLATION RATE ON PROFIT CHANGES IN CONSUMER GOODS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Wisnawati, Andi; Alam, Syamsu; Pakki, Herlina (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
This study aims to determine the effect of sales growth and the inflation rate on changes in profits in consumer goods companies listed on the Indonesian stock exchange. The population in this study totaled 26 companies obtained using the purposive sampling method for consumer goods companies during the 2017-2021 period and based on predetermined criteria, a sample of 11 consumer goods companies were obtained which were listed on the Indonesia Stock Exchange. The analytical method used is panel data analysis. The results of this study indicate that partially sales growth has a significant effect on profit changes in consumer goods companies listed on the Indonesian stock exchange, the inflation rate has a negative and insignificant effect on profit changes in consumer goods companies listed on the Indonesian stock exchange.